A randomised controlled trial of intra‐uterine insemination versus in vitro fertilisation in patients with idiopathic or mild male infertility. (28th February 2014) - Elzeiny, Hossam; Garrett, Claire; Toledo, Manuela; Stern, Kate; McBain, John; Baker, Hugh William Gordon
<x xml:space="preserve">Abstract</x> Background The cause of infertility is unexplained or poorly explained in 30–40% of couples undergoing standard investigations, and treatment ranges from expectant management to IUI and IVF. Aims The aim of this study was to compare the clinical pregnancy rates and costs of intra‐uterine insemination (IUI) and in vitro fertilisation (IVF) in women where the same ovarian stimulation led to the development of two or three mature follicles. Methods A randomised controlled clinical trial compared the efficacy of IUI and IVF in a tertiary fertility centre (ISRCTN28780587). Primary outcome measures were fetal heart positive pregnancy rate and cost per live birth. The selection criteria were age: females 18–42 years and males 18–60 years, infertility for one year or more, no IVF or IUI for 12 months prior to the trial, and no coital, tubal or ovulatory disorders, oligospermia, untreated endometriosis or contraindication for multiple pregnancy. All women (n = 102) had the same dose FSH stimulation protocol. Those who developed two or three preovulatory follicles were randomised 3:1 to IUI (n = 33) or IVF (n = 10). IUI or IVF was performed 36 h after hCG administration with single or double embryo transfer on day two. Results Clinical pregnancy rates (40% vs 12%, P = 0.04) and live birth rate (40% vs 6%, P = 0.01) were higher for IVF than IUI. The cost per live birth was AU$8735 for IVF compared with $42, 487 for IUI. Conclusions This study provides evidence that IVF is more successful and cost‐effective than IUI using the same doses of FSH. Further confirmatory studies are required.